The Role of Legal Schools in the Development of the Romano-Germanic Legal System: Peran Aliran-Aliran Hukum dalam Perkembangan Sistem Hukum Romano-Germanik - Muhammad Ibrahim Sekandary; Badam Gul Rahimi (Yayasan Nurul Musthafa, 2026)
The Roman-Germanic legal system (Civil Law) is considered one of the most important legal systems in the world, which has had a profound impact on the development of law, the organization of civil laws, and the development of legal principles. This legal system, which has historical roots in ancient Roman law, developed as a result of legal, philosophical, and scientific developments in Europe and was later transferred to many countries around the world. The study aims to evaluate and analyze the role of legal schools in the development of the Roman-Germanic legal system. The study was conducted based on the legal analysis method and used primary and secondary sources to collect data. Secondary data, scientific works, and legal theories related to the Roman-Germanic legal system, legal schools, natural law, lawmaking, and comparative law were studied. In addition, semi-structured interviews were conducted with 15 university lecturers of law faculties of private universities in Nangarhar province to analyze the practical and scientific aspects of the subject. The findings of the study indicated that the Schools of Glossators, the School of Post-Glossators, the Humanist School, the School of Natural Law, and the Enlightenment School played an important role in the intellectual, legislative, and judicial structure of the Romano-Germanic legal system. These schools played a fundamental role in the formulation of law, the organization of legal principles, the development of judicial interpretation, and the strengthening of the concepts of justice and human rights. The study also shows that the Romano-Germanic legal system still has a profound influence on contemporary civil legal systems around the world. [Sistem hukum Romano-Germanik (Civil Law) dianggap sebagai salah satu sistem hukum terpenting di dunia yang telah memberikan pengaruh besar terhadap perkembangan hukum, penyusunan hukum perdata, serta pengembangan prinsip-prinsip hukum. Sistem hukum ini memiliki akar historis dalam hukum Romawi kuno dan berkembang sebagai hasil dari perkembangan hukum, filsafat, dan ilmu pengetahuan di Eropa, yang kemudian diadopsi oleh banyak negara di berbagai belahan dunia. Penelitian ini bertujuan untuk mengevaluasi dan menganalisis peran berbagai aliran hukum dalam perkembangan sistem hukum Romano-Germanik. Penelitian dilakukan dengan menggunakan metode analisis hukum serta memanfaatkan sumber data primer dan sekunder. Data sekunder, karya-karya ilmiah, dan teori-teori hukum yang berkaitan dengan sistem hukum Romano-Germanik, aliran hukum, hukum alam, pembentukan hukum, dan hukum perbandingan dikaji secara mendalam. Selain itu, wawancara semi-terstruktur dilakukan terhadap 15 dosen fakultas hukum dari beberapa universitas swasta di Provinsi Nangarhar untuk menganalisis aspek praktis dan akademik dari topik penelitian. Hasil penelitian menunjukkan bahwa Mazhab Glossator (School of Glossators), Mazhab Pasca-Glossator (School of Post-Glossators), Mazhab Humanis (Humanist School), Mazhab Hukum Alam (School of Natural Law), dan Mazhab Pencerahan (Enlightenment School) memainkan peran penting dalam struktur intelektual, legislatif, dan yudisial sistem hukum Romano-Germanik. Aliran-aliran tersebut berperan mendasar dalam pembentukan hukum, penataan prinsip-prinsip hukum, pengembangan interpretasi yudisial, serta penguatan konsep keadilan dan hak asasi manusia. Penelitian ini juga menunjukkan bahwa sistem hukum Romano-Germanik masih memiliki pengaruh yang sangat kuat terhadap sistem hukum perdata kontemporer di berbagai negara di dunia.]